2007
DOI: 10.1074/jbc.m607016200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Interaction of the Myosin Light Chain Mlc1p with the Myosin V Myo2p IQ Motifs

Abstract: Calmodulin, regulatory, and essential myosin light chain are evolutionary conserved proteins that, by binding to IQ motifs of target proteins, regulate essential intracellular processes among which are efficiency of secretory vesicles release at synapsis, intracellular signaling, and regulation of cell division. The yeast Saccharomyces cerevisiae calmodulin Cmd1 and the essential myosin light chain Mlc1p share the ability to interact with the class V myosin Myo2p and Myo4 and the class II myosin Myo1p. These m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…Moreover, 1XO5 is a monomeric protein, and our previous NMR data are consistent with the protein being in a monomeric form in solution (12,42). The same protocol has been successfully employed in the structure determination of several other proteins (33,41,43,44). The 13 C-and 15 Nedited NOESY provided distance restraints for our structure calculation in addition to the dihedral angle, hydrogen bonds, and the RDC restraints for the protein backbone.…”
Section: Secondary Structure Of Casupporting
confidence: 62%
“…Moreover, 1XO5 is a monomeric protein, and our previous NMR data are consistent with the protein being in a monomeric form in solution (12,42). The same protocol has been successfully employed in the structure determination of several other proteins (33,41,43,44). The 13 C-and 15 Nedited NOESY provided distance restraints for our structure calculation in addition to the dihedral angle, hydrogen bonds, and the RDC restraints for the protein backbone.…”
Section: Secondary Structure Of Casupporting
confidence: 62%
“…On the basis of recent structural studies of Cdc4p and Mlc1p (the budding yeast ELC), Cam2p might be capable of simultaneously associating with Pik1p and Myo1p in a ternary complex. X-ray crystallography and NMR-based analysis of Cdc4p and Mlc1p have shown that these proteins are monomeric dumbbell-shaped molecules made up of two structurally distinct domains connected by a flexible linker (Amata et al, 2008;Escobar-Cabrera et al, 2005;Pennestri et al, 2007;Slupsky et al, 2001;Terrak et al, 2003). Mlc1p can adopt different conformations depending on the IQ motif it binds to (Terrak et al, 2003).…”
Section: Alternative Myosin-i Light Chain Cam2pmentioning
confidence: 99%
“…Mlc1p can adopt different conformations depending on the IQ motif it binds to (Terrak et al, 2003). In a 'compact' conformation both domains of Mlc1p interact with the IQ motif, whereas in an 'extended' conformation only one domain binds the IQ motif (Pennestri et al, 2007;Terrak et al, 2005;Terrak et al, 2003) leaving the other domain free to potentially bind another IQ motif on a different protein (Terrak et al, 2003). In the future it will be worth testing whether such a mechanism allows Cam2p to function with both Myo1p and Pik1p at the cortex to directly coordinate actomyosin forces with phospholipid modification at sites of endocytosis.…”
Section: Alternative Myosin-i Light Chain Cam2pmentioning
confidence: 99%
“…A second conclusion of the crystallographic studies was that the N-lobe of Mlc1p does not interact with IQ motifs 4 and 6, leaving it free to potentially interact with another binding partner. NMR studies further showed that MLC1p also binds to the first IQ motif of Myo2p only via its C-lobe, leaving the N-lobe free to bind another target [21]. In contrast, CaM binds to IQ1 with both lobes based on fluorescence resonance It includes the last three strands of the seven-stranded b sheet (magenta and yellow) and other regions that accommodate the distortion that occurs between the rigor and post-rigor states, including loop 1 (missing residues that connect the green ends), and the bulge between b strands six and seven.…”
Section: Lever Armmentioning
confidence: 99%
“…65,2008 Review Article energy transfer studies [18]. The different behavior of CaM and Mlc1p with respect to the first IQ motif of Myo2p appears to be related both to unique structural features of the N-lobe of Mlc1p, particularly the fifth D helix that stabilizes a closed lobe structure, and to the exact sequence of the IQ motif [21]. These different modes of binding may explain why Mlc1p has an essential function for vesicle targeting that is not shared by CaM.…”
Section: Lever Armmentioning
confidence: 99%